2012
DOI: 10.1093/pasj/64.3.61
|View full text |Cite
|
Sign up to set email alerts
|

A Suzaku Study of Ejecta Structure and Origin of Hard X-Ray Emission in the Supernova Remnant G 156.2+5.7

Abstract: We report on an X-ray study of the evolved Galactic supernova remnant (SNR) G 156.2$+$5.7 based on six pointing observations with Suzaku. The remnant’s large extent (100$'$ in diameter) allows us to investigate its radial structure in the northwestern and eastern directions from the apparent center. The X-ray spectra were well fit with a two-component non-equilibrium ionization model representing the swept-up interstellar medium (ISM) and the metal-rich ejecta. We found prominent central concentrations of Si, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Observationally, overionization of the X-ray-emitting plasma associated with an SNR is manifested by significant residuals that appear when spectra of the plasmas are fitted with CIE and NEI models. For example, in the case of W44, Uchida et al (2012) found significant residuals at ∼1.5 keV and ∼ 2 keV, which are attributed to the Mg-Lyα line and the Si-Lyα line, respectively. In the cases of W44 (Uchida et al 2012), IC 443 (Yamaguchi et al 2009) and G359.1-0.5 (Ohnishi et al 2011), residuals that emerged after fitting with CIE models are seen at 2.7 and 3.5 keV: lines at these energies are associated with H-like Si (2.67 keV) and H-like S (3.48 keV), respectively.…”
Section: Are the X-ray Emitting Plasmas Of These Snrs Overionized?mentioning
confidence: 97%
See 2 more Smart Citations
“…Observationally, overionization of the X-ray-emitting plasma associated with an SNR is manifested by significant residuals that appear when spectra of the plasmas are fitted with CIE and NEI models. For example, in the case of W44, Uchida et al (2012) found significant residuals at ∼1.5 keV and ∼ 2 keV, which are attributed to the Mg-Lyα line and the Si-Lyα line, respectively. In the cases of W44 (Uchida et al 2012), IC 443 (Yamaguchi et al 2009) and G359.1-0.5 (Ohnishi et al 2011), residuals that emerged after fitting with CIE models are seen at 2.7 and 3.5 keV: lines at these energies are associated with H-like Si (2.67 keV) and H-like S (3.48 keV), respectively.…”
Section: Are the X-ray Emitting Plasmas Of These Snrs Overionized?mentioning
confidence: 97%
“…For example, in the case of W44, Uchida et al (2012) found significant residuals at ∼1.5 keV and ∼ 2 keV, which are attributed to the Mg-Lyα line and the Si-Lyα line, respectively. In the cases of W44 (Uchida et al 2012), IC 443 (Yamaguchi et al 2009) and G359.1-0.5 (Ohnishi et al 2011), residuals that emerged after fitting with CIE models are seen at 2.7 and 3.5 keV: lines at these energies are associated with H-like Si (2.67 keV) and H-like S (3.48 keV), respectively. Finally, in the case of W49B, Ozawa et al (2009) identified residuals at the energies of 5.6, 6.2, 6.7, 6.9, 7.9, 8.5 keV: these lines are attributed to Cr Kα, Mnα and four Fe lines (of Heα rec , Lyα, Heβ rec and Heγ), respectively.…”
Section: Are the X-ray Emitting Plasmas Of These Snrs Overionized?mentioning
confidence: 97%
See 1 more Smart Citation